Attribution of observed historical near‒surface temperature variations to anthropogenic and natural causes using CMIP5 simulations. Issue 10 (21st May 2013) - Jones, Gareth S.; Stott, Peter A.; Christidis, Nikolaos
Abstract : [1] We have carried out an investigation into the causes of changes in near‒surface temperatures from 1860 to 2010. We analyze the HadCRUT4 observational data set which has the most comprehensive set of adjustments available to date for systematic biases in sea surface temperatures and the CMIP5 ensemble of coupled models which represents the most sophisticated multi‒model climate modeling exercise yet carried out. Simulations that incorporate both anthropogenic and natural factors span changes in observed temperatures between 1860 and 2010, while simulations of natural factors do not warm as much as observed. As a result of sampling a much wider range of structural modeling uncertainty, we find a wider spread of historic temperature changes in CMIP5 than was simulated by the previous multi‒model ensemble, CMIP3. However, calculations of attributable temperature trends based on optimal detection support previous conclusions that human‒induced greenhouse gases dominate observed global warming since the mid‒20th century. With a much wider exploration of model uncertainty than previously carried out, we find that individually the models give a wide range of possible counteracting cooling from the direct and indirect effects of aerosols and other non‒greenhouse gas anthropogenic forcings. Analyzing the multi‒model mean over 1951–2010 (focusing on the most robust result), we estimate a range of possible contributions to the observed warming of approximately 0.6 K from greenhouse gases of between 0.6 and 1.2 K, balanced by a counteracting cooling from other anthropogenic forcings of between 0 and −0.5 K. Key Points: Latest dataset of historic temperatures compared with multi model ensemble CMIP5 models have wider range of global mean warming than CMIP3 models Multimodel attribution analysis shows greenhouse gases dominate warming